Rancang Bangun Sistem E-Survey Berbasis Web dengan Fitur Speech-to-Text Menggunakan Metode Waterfall - M. Aziz Kurniawan; Yumna Zahran Ramadhan; Muhammad Solehuddin; Deki Satria; Sasmi Hidayatul Yulianing Tyas (LPPM Universitas Bhinneka Nusantara, 2026)
Web-based electronic survey systems are widely used in higher education due to their efficiency and flexibility in data collection. However, many existing survey platforms still rely on conventional text-based input and provide limited accessibility support for users with disabilities. This study aims to develop a web-based E-Survey system integrated with a speech-to-text feature to improve accessibility and support inclusive participation in digital survey activities. The system was developed using the System Development Life Cycle (SDLC) with the Waterfall method, covering requirements analysis, system design, implementation, and testing. Accessibility considerations were based on the Web Content Accessibility Guidelines (WCAG) 2.1, while speech-to-text functionality was implemented using Automatic Speech Recognition (ASR) technology. System evaluation included black box testing, WCAG-based accessibility assessment, and speech-to-text performance testing using Accuracy and Word Error Rate (WER) metrics. The results indicate that all selected accessibility criteria evaluated in this study were successfully implemented and were consistent with the selected WCAG 2.1 principles assessed through developer-based inspection. The speech-to-text feature achieved an accuracy rate of 85.71% and a Word Error Rate (WER) of 5.41%. These findings demonstrate that the proposed system provides a more accessible and inclusive survey environment by enabling respondents to complete surveys through text or voice input, while highlighting the potential of speech-to-text technology in supporting inclusive participation in higher education.